Evaluating cloud seeding initiatives for sustainable water supply in arid environments: insights from Al Baha, Saudi Arabia - Abdulaziz S. Alzahrani; Ahmed M. Abdelbaki (Ain Shams Engineering Journal, 2025)
Water scarcity poses a significant challenge in arid regions worldwide, prompting exploration of weather modification techniques like cloud seeding as potential solutions. This study evaluates the impact of a cloud seeding operation conducted on August 4, 2022, in Southern Saudi Arabia, assessing precipitation changes over five to six months in three cities: Al-Makhwah, Al-Baha, and Al-Mandaq. A comparison of rainfall amounts before and after cloud seeding indicate substantial increases in monthly rainfall—61.62 mm (253 %) in Al-Makhwah, 63.2 mm (550 %) in Al-Baha, and 61.63 mm (287 %) in Al-Mandaq—along with an increase in rainy days. Particularly for Al-Baha, which heavily relies on dams and groundwater, cloud seeding may enhance both rainfall frequency and volume. However, while promising, cloud seeding is not a comprehensive fix for drought or water scarcity. It is essential to weigh the environmental, health, and economic implications of this technology when considering its broader application.